MANEUVER CONTROL OF UNMANNED COMBATANT AERIAL VEHICLE (UCAV) USING UNCONVENTIONAL EFFECTOR - Ekananto, Rayhan
The QF-4 Phantom is considered to be an Unmanned Combatant Aerial Vehicle (UCAV) derived from a fighter jet capable of uncommon maneuver in which regular aircrafts may not be able to do. Maneuvers vary in accordance with the requirement and the flight condition, but in general the aircraft needs to have a certain resistance against stall, spin, and other flight dynamic obstacles. One method that are commonly used in fighter aircrafts is the installation of unconventional effectors which include but not limited to Thrust Vectoring Control (TVC), thrust, winglet, and canard. These unconventional effectors vary in size and function in accordance with what the aircraft is trying to achieve. Which is why, a switching flight control system applied to both conventional and unconventional needs must be installed in order for the aircraft to independently choose the most effective and optimized effector that needs to be used for certain flight and maneuvering conditions. The method of determining which effector to use is by conducting a numerical and computational simulation using MATLAB and Simulink software and basing on the principles of multivariable control. The dynamical model of the QF-4 Phantom is also created in which is trimmed and linearized according to the desired conditions and then applied back to the non-linear model in which switching can be done. The results of the study indicate that for the 3DoF Model of the QF-4 Phantom aircraft, the combinations of ?T (Thrust) – ?ptv (pitch-thrust vectoring) are the most effective in achieving trim holding. These combinations quickly and accurately trim both the angle of attack (?) and flight path angle (?) signals. On the other hand, combinations of ?E (Elevator) – ?ptv are not capable of simultaneously trimming both signals, as they result in lower pitch angles and slower descent rates. Finally, the combinations of ?E – ?T are similar to ?T – ?ptv but much better after switching which is in lower height and velocities. Meanwhile, the 6DoF Model of the aircraft uses effector inputs of thrust, pitch-thrust vectoring, and yaw-thrust vectoring which when applied to a non-linear model, tends to stray further in the x-direction, or yaw to the right. These findings shed light on the effectiveness and limitations of different effector combinations for maneuver control in UCAVs.